(Re)Forming Unions for Social Justice: A Critical Autoethnographic Inquiry into Racism, Democracy, and Teacher Leadership - Owens, Leah Z. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
Within the contemporary anti-union environment fueled by neoliberalism, teachers are organizing and educating each other in order to push back against the corporate reform agenda and envision a public education that supports all students. Using a critical autoethnography methodology, the author narrates her participation in social justice unionism through a series of episodes and then performs the analytical practice of co-reading with critical social theories. This article illuminates intersections of democracy and racism with neoliberal education reform and practices of teacher leadership. It concludes with implications for social justice caucuses and social justice unionism.